2023
DOI: 10.1111/apt.17424
|View full text |Cite
|
Sign up to set email alerts
|

Higher mortality among lean patients with non‐alcoholic fatty liver disease despite fewer metabolic comorbidities

Abstract: Background & Aims: Non-alcoholic fatty liver disease (NAFLD) can develop in individuals who are not overweight. Whether lean persons with NAFLD have lower mortality and lower incidence of cirrhosis, cardiovascular diseases (CVD), diabetes mellitus (DM) and cancer than overweight/obese persons with NAFLD remains inconclusive. We compared mortality and incidence of cirrhosis, CVD, DM and cancer between lean versus non-lean persons with NAFLD.Methods: This is a retrospective study of adults with NAFLD in a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
44
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 49 publications
3
44
0
Order By: Relevance
“…Recently, a meta-analysis by Ha et al reported that lean NAFLD had comparable risks of all-cause mortality, cardiovascular mortality and liver events, but had higher risk of liver diseasespecific mortality. 9 Karn and colleagues 10 have compared the baseline characteristics between lean and non-lean NAFLD patients and also analysed longitudinally the mortality and clinical outcomes between these two groups of patients. They utilised a validated natural language processing algorithm, which identified >13,000 patients with NAFLD through ultrasonographic, transient elastography or biopsy reports.…”
Section: N V I T E D E D I T O R I a L Editorial: Clinical Outcomes I...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a meta-analysis by Ha et al reported that lean NAFLD had comparable risks of all-cause mortality, cardiovascular mortality and liver events, but had higher risk of liver diseasespecific mortality. 9 Karn and colleagues 10 have compared the baseline characteristics between lean and non-lean NAFLD patients and also analysed longitudinally the mortality and clinical outcomes between these two groups of patients. They utilised a validated natural language processing algorithm, which identified >13,000 patients with NAFLD through ultrasonographic, transient elastography or biopsy reports.…”
Section: N V I T E D E D I T O R I a L Editorial: Clinical Outcomes I...mentioning
confidence: 99%
“…Karn and colleagues 10 have compared the baseline characteristics between lean and non‐lean NAFLD patients and also analysed longitudinally the mortality and clinical outcomes between these two groups of patients. They utilised a validated natural language processing algorithm, which identified >13,000 patients with NAFLD through ultrasonographic, transient elastography or biopsy reports.…”
mentioning
confidence: 99%
“…The authors' declarations of personal conflicts of interest are unchanged from those in the original article 2 …”
Section: Conflict Of Interest Statementmentioning
confidence: 99%
“…
We read with great interest the editorial by Tan et al 1 on our recent study on clinical outcomes in patients with lean non-alcoholic fatty liver disease (NAFLD), where we found that lean patients with NAFLD experienced higher mortality than patients with overweight or obesity, despite lower prevalence of baseline metabolic disease and lower incidence of cirrhosis and diabetes.We would like to clarify how our cohort was generated and the rationale for this approach. 2 We identified patients with hepatic steatosis based on simple natural language processing algorithms applied to imaging, biopsy, and vibration-controlled transient elastography re-Medicine
…”
mentioning
confidence: 99%
See 1 more Smart Citation